Constraints versus adaptations as contending evolutionary explanations of morphological structure : The giraffe (Giraffa Camelopardalis) head and neck as a heuristic model - Badlangana, Ludo Nlambiwa (My University, 2008)
The current study uses the head and neck of giraffe (Giraffa camelopardalis) as a model for tracking the course of evolutionary change. Gould (2002) has argued that there are three main avenues of evolutionary change that result in the genesis of new morphologies. These are phylogenetic constraints, structural or allometric scaling laws of form, and specific unique adaptations. It is well known that the unique characteristic of the giraffe is its extremely long neck and yet, it only has seven cervical vertebrae. To study the neck the vertebral body lengths of different aged giraffes were measured to determine the contribution of the cervical vertebrae to the total vertebral column. The vertebrae of several extant ungulates as well as those of fossil giraffids were used as a comparison with the giraffe. CT scans were used on several giraffe skulls to study the extent of the frontal sinus in the giraffe in an attempt to explain why the giraffe evolved such a large frontal sinus. The vertebral columns and skulls of several ungulates, including the okapi (Okapia johnstoni) were also used to compare with the results obtained from the giraffe. Immunohistochemistry was used to study the medulla and spinal cord sections of the giraffe to determine if the location and size of the nuclei remained unchanged to the basic ungulate or mammalian plan in spite of the unusually long neck, or if this long neck led to changes in the nuclei found in those regions. The results of these stains were all compared to the published literature available. Although more studies need to be conducted on other ungulates to conclusively determine why giraffe have evolved a long neck, overall the results showed that the anatomy giraffe head and neck remained true to the basic mammalian plan, with very little changing in terms of it morphology. The giraffe brain and spinal cord also resembled that of a typical ungulate. This leads to the conclusion that constraints and allometric scaling laws of form play a greater role than previously thought in the evolution of extreme morphologies.
Keywords: Giraffidae; cervical vertebrae; frontal sinus; spinal cord; evolution; neuromodulatory systems; dopamine; noradrenalin; serotonin; Mammalia